Silkfibroin-Ca-P composite bone replacement material for guided bone growth - (:unkn) unknown (International Committee on Composite Materials, 2015)
Mineralized natural protein based materials are investigated as novel materials to be used in tissue engineering and as bone replacement materials. Silk fibroin fiber based foams and films are used as mineralized composites due to their excellent biocompatibility. In this study, the biomimetic mineralization of orderly oriented fibrous silk based scaffolds was studied. Commercially obtained pure silk woven fabric was boiled in 0.02 M Na2CO3 for 20 min. The deposition of calcium phosphate was conducted at 37°C for twenty minutes in seven sequential immersion steps in 250 mM CaCl2 2H2O and 120 mM K2HPO4, both containing 0.15 M NaCl and 50mM solution of TRIS-HCl, buffered at 7.4. Ca-P deposit on the samples increased with the number of immersion steps. The analysis of the Ca-P powder deposit indicated formation of brushite with its characteristic peak at around 11.76 2θ using the XRD and at 1000, 3000-3500 cm-1 using the FTIR analyses. Samples were sputter coated with gold for SEM characterization. The morphology of the Ca-P deposits confirmed formation of brushite crystals, which were then transformed into HA using electrochemical hydrothermal treatment in concentrated SBF solution 40°C at a current density of -25mA/cm2 for 60 min. HA formation was confirmed using XRD, FTIR and SEM analysis. The deposition and electrochemical conversion of brushite to hydroxyapatite on silk, thus forming a silk-HA composite material may be an inexpensive. © 2015 International Committee on Composite Materials. All rights reserved.
Keywords: Bone replacement materials; Composite materials; Hydroxyapatite; Silk scaffold; Tissue engineering